STRESSORS OF THE STUDY PROCESS, THEIR EMPIRICAL RESEARCH AT RĒZEKNE ACADEMY OF TECHNOLOGIES - Kalvans, Eriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This scientific article presents a theoretical review of stress factors of young students and the results of empirical research of these factors at the Rezekne Academy of Technologies. The need for such research is justified by International studies (n=540 000), in which was found that the study process causes high level of stress in 37% of students. The results of other studies in different countries also show that the prevalence and severity of mental problems among students is increasing. Overall, these studies indicate that students are increasingly experiencing symptoms of increased anxiety and stress, as well as depression. Thus, increase in student stress levels and related deterioration of students' psychological well-being is a major challenge in today's higher education institutions. Taking into account the mentioned findings, the aim of this article is to identify the most common stress factors in the study process at the Rezekne Academy of Technologies. The analysis of scientific literature and empirical results were used as basic methods in the development of the article.